Cribriform Plate Injury After Nasal Swab Testing for COVID-19 - Knížek, Zdeněk; Michálek, Roman; Vodička, Jan; Zdobinská, Pavlína (American Medical Association, 2021)
In March 2020, the World Health Organization characterized the spread of coronavirus disease (COVID-19) as a pandemic. A lot of nasal swabs were used to diagnose COVID-19 to detect the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the upper respiratory tract. We present a case of cerebrospinal fluid (CSF) leak after skull base injury following nasal swab testing for COVID-19 in a patient with a previously intact skull base.
Poranění cribriformní desky po testování nosním výtěrem na COVID-19.
Keywords: cribriform plate injury; nasal swab testing; COVID-19; poranění cribriformní desky; testování nosním výtěrem; COVID-19